2014
DOI: 10.2174/1389202915666140516204512
|View full text |Cite
|
Sign up to set email alerts
|

Using Current Data to Define New Approach in Age Related Macular Degeneration: Need to Accelerate Translational Research

Abstract: Age related macular degeneration (AMD) is one of the major retinal degenerative disease of ageing whose complex genetic basis remains undeciphered. The involvement of various other factors like mitochondrial genes, cytoskeletal proteins and the role of epigenetics has been described in this review. Several population based AMD genetic studies have been carried out worldwide. Despite the increased publication of reports, clinical translation still eludes this davastating disease. We suggest models to address ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Diseases affecting the posterior segment of the eye are devastating and cause blindness in many patients. In recent decades, highly developed countries have witnessed a dramatic increase in the incidence of such pathologies, especially in those which are age-related (Anand 2014). These include uveitis (Miserocchi 2013), proliferative diabetic retinopathy (Sapieha 2010), macular oedema (Zhang 2014) and macular degeneration associated with age (AMD) (van Wijngaarden 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Diseases affecting the posterior segment of the eye are devastating and cause blindness in many patients. In recent decades, highly developed countries have witnessed a dramatic increase in the incidence of such pathologies, especially in those which are age-related (Anand 2014). These include uveitis (Miserocchi 2013), proliferative diabetic retinopathy (Sapieha 2010), macular oedema (Zhang 2014) and macular degeneration associated with age (AMD) (van Wijngaarden 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Neovascularization underlying choroid can percolate the Bruch’s membrane and disrupt the integrity of retinal pigment epithelium (RPE) layer. Neovascularization process is guided by several angiogenic factors including Platelet-derived growth factor (PDGF) 1 , 2 , matrix metalloproteinases (MMPs), 3 , 4 Pigment epithelium-derived factor (PEDF) 5 , TGF-β and its receptors. 6 , 7 Among all, vascular endothelial growth factor (VEGF) is more potent to lead angiogenic process.…”
Section: Introductionmentioning
confidence: 99%
“…Although, it has been found that TGF-β could induce the VEGF expression in RPE cells, with the involvement of MAP kinases, signifies the role of TGF beta as the pro-angiogenic protein in enabling angiogenic process. 8 Apart from these angiogenic factors, several pro-angiogenic factors (TIMPs family and FGF) 3 , 4 are also involved in the process. Hence, neovascularization is a complex process having role of both angiogenic and pro-angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is not ignorance or reluctance of ophthalmologists, but rather the lack of translational studies transferring the genomic findings from basic research to clinical research, and from there to evidence-based recommendations for implementation in practice [47]. Anand et al describe that although the number of population-based genetic studies in AMD is increasing every year, most of these findings have not been translated into development of human diagnostic, prognostic and pharmaceutical applications [48]. For example, future studies may investigate whether individuals tested for AMD genes have a lower risk of developing the manifest disease when adhering to a preventive lifestyle, and whether knowing their risk affects their quality of life.…”
Section: Discussionmentioning
confidence: 99%